Intervenções de enfermagem propostas pela nursing interventions classification (NIC) para o diagnóstico de enfermagem integridade da pele prejudicada em recém-nascidos - Fontenele, Fernanda Cavalcante (2013)
The assistance to newborns with impaired skin integrity should be a priority for the nursing staff. Thus, we aimed to analyze the use of the interventions proposed by the Nursing Intervention Classification (NIC) indicated for the nursing diagnosis Impaired skin integrity in the Neonatal Intensive Care Unit. This is an exploratory descriptive study using cross-mapping in three public neonatal units, in Fortaleza-CE, Brazil. The population was composed of 42 nurses working in neonatology. Data collection was conducted from May to September 2011, according to the availability of participants. The study was approved by the Ethics Committee of the institutions surveyed. In the first moment of collection, nurses indicated the activities they performed along with the newborns with the nursing diagnosis Impaired skin integrity. Next, we compared these activities with the interventions proposed by NIC, characterizing the mapping. The analysis occurred between October 2011 and January 2012. To review and refinement of the mapping, the results obtained were sent to nine nurses experts in nursing diagnosis through conventional mail and e-mail. The mapping revealed that from the 75 activities suggested by NIC, 57 corresponded to those indicated by nurses. The most mentioned by nurses as routinely performed were related to the care of injuries: apply an adequate bandage for the type of injury; reposition the patient at least once every two hours, as recommended; positioning the patient in order to avoid tension on the injury, as recommended; and remove bandage and tape. Topical Treatment: apply moisturizers to the affected area; apply a transparent occlusive dressing when necessary; and avoid the use of alkaline soap on the skin. Skin surveillance: examine the skin and mucous membranes for redness, excessive heat, edema and drainage, and document changes in the skin and mucous membranes. The activities suggested by NIC most performed according to the nurses’ opinion (weighted average of 0.8-1) related to the care of injuries were: apply an appropriate bandage for the type of injury; maintain aseptic technique during performance; changing dressings according to the amount of exudate and draining; cleaning with saline or non-toxic substances; positioning the patient in order to prevent tension on the wound; and reposition the patient at least once every two hours. As regards to topical treatment: keep bed linen clean, dry and wrinkle-free; apply transparent occlusive dressing; provide intimate hygiene; apply topical antibiotics to the affected area; and apply moisturizer to the affected area. As for the skin surveillance: observe the extremities for color, warmth, swelling, pulses, texture, edema and ulceration; monitor skin color and temperature; and examine the condition of the surgical incision. After submitting the mapping to the evaluation of expert nurses, it was suggested that, of the 22 activities of skin care, 13 remain with the NIC taxonomy. Regarding the topical treatment, 23 activities had minor changes and 10 remained unchanged. On the skin surveillance, 3 activities were modified and 9 kept the NIC taxonomy. We concluded that is possible to use the NIC as a standardized terminology to describe the nursing care prescribed, once this classification has proven, in most cases, appropriate to neonatal reality.